2010
DOI: 10.1007/s00482-010-1000-5
|View full text |Cite
|
Sign up to set email alerts
|

Leben retten – sterben zulassen

Abstract: Every emergency physician can be confronted with an emergency involving a patient with a progressive incurable disease. The condition of each patient must be assessed for each medical decision. Not only medical, but also psychosocial, ethical and legal aspects have to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
0
4
0
4
Order By: Relevance
“…(5) Early implementation of “End-of-Life” conversations to define a palliative care patient [27-29]. …”
Section: Discussionmentioning
confidence: 99%
“…(5) Early implementation of “End-of-Life” conversations to define a palliative care patient [27-29]. …”
Section: Discussionmentioning
confidence: 99%
“…Challenges associated with working conditions, such as fast-paced work environment, the need for rapid treatment decisions, as well as a lack of patient-physician relationship seen in in hospital emergency care [2327], were also repeatedly mentioned by EPs in our study. Other studies had observed significantly longer mean durations of emergency care visits in patients with advanced incurable diseases in their familiar home environment, which might result from emergency physicians' doubts to leave the patients in an insecure situation at home [35]. In our study, EPs indicated fear of legal consequences.…”
Section: Discussionmentioning
confidence: 47%
“…However, the literature has stressed the pitfalls of escalation of these life-preserving interventions and of losing sight of the rationale of hospice care to guide patient and family towards nearing death [22,23]. Wright et al.…”
Section: Discussionmentioning
confidence: 99%